Effect of Small Impoundments on Leaf Litter Decomposition in Streams - Mbaka, John Gichimu; Schäfer, Ralf Bernhard (John Wiley & Sons, Ltd, 2015)
Leaf litter decomposition is an important process providing energy to freshwater biota. Flow regulation and dams can strongly alter freshwater ecosystems, but little is known about the effect of small impoundments on leaf litter decomposition rates in headwater streams. In this study, we examined the effect of small water storage impoundments (80 to 720 m3) on leaf litter decomposition by comparing sites located within 10-m upstream and downstream of nine impoundments (Rhineland Palatinate, Germany) and sites located further upstream and downstream. The impoundments did not have a statistically significant effect on most physico-chemical variables. However, the abundance of shredders and leaf litter decomposition rates decreased in study sites located within 10-m upstream of the area flooded by impoundments. Small impoundments can locally reduce leaf litter decomposition rates in headwater streams. The effect of small impoundments on ecosystem functioning is minor and may require less attention by freshwater managers than other stressors, though this may differ for other ecological aspects such as connectivity.
Keywords: Shredder; Headwater stream; Stream ecosystem functioning; Damming; Leaf litter breakdown; Alder tree